A dimeric PR‐1‐type pathogenesis‐related protein interacts with ToxA and potentially mediates ToxA‐induced necrosis in sensitive wheat. (15th April 2014) - Lu, Shunwen; Faris, Justin D.; Sherwood, Robert; Friesen, Timothy L.; Edwards, Michael C.
Summary A dimeric PR‐1‐type pathogenesis‐related protein (PR‐1‐5), recently identified in wheat, was found to interact with Stagonospora nodorum ToxA in both yeast two‐hybrid and co‐immunoprecipitation assays. Site‐specific mutational analyses revealed that the RGD motif of ToxA is not targeted by PR‐1‐5, whereas two surface‐exposed asparagine residues are essential for the interaction: the N102 residue of the turning loop between β2 and β3 in ToxA and the N141 residue of the turning loop between βC and βD in PR‐1‐5. Recombinant PR‐1‐5 and ToxA mutant proteins carrying alanine substitutions at the interacting sites were expressed in Pichia pastoris, together with the wild‐type proteins. Native polyacrylamide gel electrophoresis (PAGE) confirmed that the PR‐1‐5‐N141A mutant retains the ability to form dimers. Plant assays indicated that the ToxA‐N102A mutant fails to induce necrosis, whereas the PR‐1‐5‐N141A mutant is impaired in the 'necrosis‐promoting' activity shown by the wild‐type PR‐1‐5 when co‐infiltrated with ToxA in sensitive wheat. Reverse transcriptase‐polymerase chain reaction and Western blot analyses revealed that the native PR‐1‐5 protein is differentially expressed between ToxA‐sensitive and ToxA‐insensitive wheat lines in response to ToxA treatment. These results suggest that PR‐1‐5 is a potential target of ToxA and the site‐specific interaction between PR‐1‐5 and ToxA may mediate ToxA‐induced necrosis in sensitive wheat.